Pengembangan Media Digital sebagai Strategi Retorika Pemasaran Produk Resin Eco-Kultural Sigur.id di Desa Branjang, Ungaran Barat - Agustin, Evi Yanti; Handaka, Theresia Rachel Aurelia; Saputri, Novellia Shafa Nur; A'la, Muhammad Faishal Rofiqil; Tedja, Muthia Fakhira; Devitasari, Rafaela Tiara; Patricia, Aretha Hanny; Nasution, Irzan Althaf Munif; Rachmadhani, Aulia; Mukafi, Muhammad Hamdan; Komariya, Siti; Pramudyo, Gani Nur (Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
The purpose of this study is to evaluate the effectiveness of digital media in building cultural narratives while strengthening the position of UMKM products in the creative economy ecosystem. The method used is a mixed-methods approach, which combines qualitative and quantitative approaches simultaneously. Qualitative data were collected through semi-structured interviews, participant observation, and visual documentation, while quantitative data were obtained from social media insights, website metrics, and e-commerce performance. The literature review includes Aristotle's rhetorical theory (ethos, pathos, logos), the concept of MSME digitalization, and the eco-cultural storytelling approach. The results of the study show that digital media not only function as a promotional tool but also as a medium for preserving culture and forming the identity of local products. The rhetorical strategy applied was successful in creating emotional, logical, and credible engagement with the audience. In conclusion, the integration between technology and cultural values through a marketing rhetoric approach is able to build sustainable MSME positioning while strengthening a more meaningful digital cultural ecosystem.